ACCOUNTING IN THE CURRICULUM OF THE SMALL LIBERAL ARTS COLLEGE. - Campbell, James A. (The Accounting Review, 1930)
Abstract An Interesting situation exists at the present time with reference to the position of accounting in the curriculum of the small Liberal Arts College in the United States. The selection was made from the catalogs on file in the Business Office of Knox College, and the only principle observed was to pick institutions with less than one thousand students offering a liberal arts course. The resulting group of one hundred three colleges is merely a fair sample or cross section of American Colleges, and no claim is made for completeness or finality. Certain titles, such as Banking, Investments, Labor, Insurance, Marketing, Public Finance and Business Law offer no difficulty for they are applied to practically the same subject matter in all cases. There is another fact about the selection of courses, which should be stated. It is based on courses advertised in the catalog, not on courses taught. If Natural Science is tinctured with Business, as in the case of Economic Geology it often proves an attractive lure. The number of times a week that a course meets was not considered.